Criteria for selecting patients with resistant hypertension for a renal sympathetic denervation - T M Ripp; T Yu Rebrova; V F Mordovin; S A Afanasiev; S E Pekarsky; G V Semke; A Yu Falkovskaya; V A Lichikaki; E V Tsymbalyuk (Терапевтический архив, 2016)
Aim. To define and develop a procedure that can select patients with resistant hypertension (RH) for a renal sympathetic denervation (RSD) procedure, by being orienting to the specific initial values of β-adrenoreactivity (β-AR) and systolic blood pressure (SBP). Subjects and methods. The analysis included 23 RH patients receiving the maximally tolerable doses of 4 antihypertensive drugs. The investigations involving BP control and a Russian spectrophotometric procedure for determining β-AR in terms of the change in the osmoresistance of erythrocyte membranes (EM) were performed at baseline and 4 and 24 weeks. RSD was carried out using endovascular radiofrequency ablation of the renal arteries. The therapy was not changed during the observation. Results. If SBP was >170 mm Hg and β-AR of EM >40 conditional units (CUs) at baseline, ΔSBP was 17.68±3.24 mm Hg and the efficiency of RSD was 100%. When SBP was